2015
DOI: 10.1097/fjc.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 Mediates the Delayed Cardioprotection of Hypoxic Preconditioning Through Activation of Nrf2 and Subsequent Upregulation of Antioxidative Enzymes

Abstract: We have recently shown that DJ-1 is implicated in the delayed cardioprotective effect of hypoxic preconditioning (HPC) against hypoxia/reoxygenation (H/R) injury as an endogenous protective protein. This study aims to further investigate the underlying mechanism by which DJ-1 mediates the delayed cardioprotection of HPC against H/R-induced oxidative stress. Using a well-characterized cellular model of HPC from rat heart-derived H9c2 cells, we found that HPC promoted nuclear factor erythroid 2-related factor 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…DJ‐1 is known to be present in the heart and only recently has its cardioprotective role in myocardial I/R injury been uncovered through a DJ‐1‐antioxidative stress pathway . Notably, the important role of DJ‐1 as a potential mediator of IPC has been investigated in our recently published experimental studies . In the present study, this is again confirmed by the better cell viability with the less LDH release in DJ‐1 overexpressing H9c2 cells subjected to H/R and disappeared cardioprotection of DHP in DJ‐1 knockdown H9c2 cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…DJ‐1 is known to be present in the heart and only recently has its cardioprotective role in myocardial I/R injury been uncovered through a DJ‐1‐antioxidative stress pathway . Notably, the important role of DJ‐1 as a potential mediator of IPC has been investigated in our recently published experimental studies . In the present study, this is again confirmed by the better cell viability with the less LDH release in DJ‐1 overexpressing H9c2 cells subjected to H/R and disappeared cardioprotection of DHP in DJ‐1 knockdown H9c2 cells.…”
Section: Discussionsupporting
confidence: 82%
“…31,32 Notably, the important role of DJ-1 as a potential mediator of IPC has been investigated in our recently published experimental studies. 9,10,33 In the present study, this is again confirmed by the better cell viability with the less LDH release in DJ-1 overexpressing H9c2 cells subjected to H/R and disappeared cardioprotection of DHP in DJ-1 knockdown H9c2 cells. Moreover, the present study also showed that DHP attenuated H/R-induced oxidative stress in a DJ-1-dependent way.…”
Section: Dj-1 Contributes To the Inhibitory Effect Of Dhp On H/r-insupporting
confidence: 83%
“…Excessive generation of ROS is involved in several detrimental processes, including cell death and apoptosis triggered by the opening of the mitochondrial permeability transition pores (mPTP) [ 6 , 7 ]. Antioxidant agents can effectively decrease generation of ROS, therefore, antioxidant therapy, especially activation of endogenous antioxidant enzymes, such as catalase and manganese superoxide dismutase (MnSOD) seems to be a potential therapeutic approach for myocardial IR injury [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The important role of DJ-1 as a potential mediator of HPC has been investigated in ours previous published experimental works, and studies have shown that DJ-1 is implicated in the cardioprotection of HPC against H/R-induced oxidative stress damage [6,8,25]. Interestingly, our recent studies have demonstrated that DJ-1-mediated cardioprotection is related to preserving mitochondrial complex I activity and subsequently inhibiting mitochondrial ROS generation [15].…”
Section: Discussionmentioning
confidence: 90%
“…A wealth of information has been collected on the molecular mechanisms involved in ischemic preconditioning, but many aspects of the signaling pathways and of the end effectors of the cardioprotection remain unknown [2,4,5]. An intriguing and unresolved aspect is the involvement of DJ-1 in the genesis of preconditioning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%